The Effects of Blockchain Technology Adoption on Business Ethics and Social Sustainability: Evidence from Chinese FinTech Companies - Yu, Wenbo (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: Blockchain is a disruptive technology that significantly improves transactions through enhanced transparency, security, traceability, and smart contracts. Although the technology consumes significant energy to produce, it has positively impacted social sustainability. This study examined the effects of blockchain technology adoption on business ethics and social sustainability. Materials and Methods: Data was obtained from 247 CEOs and managers of fintech and financial companies. Out of the 300 electronic questionnaires that were sent to the CEOs, a total of 247 were completed and returned. The obtained P-value (<0.05) showed that the hypotheses were accepted at a 95% confidence level. Results: The results showed that blockchain adoption positively impacts business ethics and social sustainability. The results also showed that business ethics has positive effects on social sustainability. Key managerial implications include policy formulations to enhance blockchain adoption and stakeholder onboarding. Conclusion: The results indicate that blockchain adoption enhances transparency, security, traceability, and smart contracts in business or financial transactions. The study encourages businesses to adopt blockchain technologies to prevent fraud in financial transactions. Blockchain technology enables businesses to build trust through data sharing and transparency.